Perspectives of adults living with HIV attending the opportunistic infections clinic at Chitungwiza central hospital in Zimbabwe towards physical activity: a cross-sectional survey - Farayi Kaseke; Precious R Pamire; Tecla Mlambo; Clement Nhunzvi (BMC, 2023)
Abstract Background Regular physical activity and exercise have been shown to be of benefit in managing the HIV disease, its complications and the side effects of HAART. The perceptions of those living with HIV toward physical activity and exercises is a key factor in advocating for participation of rehabilitation personnel in the management of this disease. However, this domain remains underexplored in Zimbabwe. Methods A descriptive cross-sectional quantitative study was conducted with 327 people living with HIV. Participants were consecutively sampled from Chitungwiza Central Hospital Opportunistic Clinic. The International Physical Activity Questionnaire (IPAQ) and the Exercise Benefits/Barriers Scale (EBBS) were respectively used to measure the physical activity level and perceived benefits/barriers of physical exercise among adults living with HIV. The tools were self-administered. The analyses were done for 323 participants using the Statistical Package for the Social Sciences (SPSS). Results The mean age was 41.1 ± 11.0. Females constituted 69.7% (n = 225) of the sample. The majority of participants (n = 184; 57%) described themselves as being highly physically active (3204;IQR = 2139-4441 MET-minutes/week). Most of the participants agreed that physical activity prevented heart attacks with a mean value of 3.34 ± 0.65. The majority perceived psychological outlook as the greatest benefit from physical activity among the benefit sub-scales. Furthermore, most of the participants agreed that it cost too much for them to exercise which had a mean of 3.00 ± 0.88. Family discouragement was the most agreed perceived barrier to physical activity with a mean of 2.91 ± 0.67. Those who perceived physical activity as being beneficial reported less barriers. A statistically significant association was found between level of physical activity and CD4 cell count (p = 0.035) as well as with employment status (p < 0.05). No statistically significant association was reported between the perceived benefits and the level of physical activity (p = 0.214). A statistically significant association was reported between the perceived barriers and age (p < 0.05) as well as with employment status (p = 0.006). Conclusion Adults living with HIV receiving HAART at Chitungwiza Central Hospital are highly active when compared to other studies done in Sub-Saharan Africa. It is also important to create interventions that promote physical activity considering what this population considers as perceived benefits and barriers to physical activity.